ANALISIS EARNED VALUE TERHADAP BIAYA DAN WAKTU PADA PROYEK PEMBANGUNAN RUANG KELAS BARU MADRASAH TSNAWIYAH NEGERI 6 MALUKU TENGAH - Walalayo, Elis; Saleh , La Mohamat; Gaspersz , Willem (Journal Agregate, 2024)
In project implementation, project completion often occurs that is not under planning both in terms of time, cost, and quality, as well as over budget, so to overcome this, good project management is needed in the form of time, cost, and quality control. on the New Classroom Construction Project for Madrasah Tsnawiyah Negeri 6 Central Maluku located in Liang Village, Kec. Salahutu, Kab. Central Maluku which has a budget of Rp. 2,998,745,000.00 with a planned implementation time of 126 calendar days from June to October 2022 but the realization of the project was late and was completed in 168 calendar days. To overcome this problem, the author uses the earned value method. The Earned Value method is a control method used to control project costs and time in an integrated manner. From the results of the last analysis in the 24th week, the work cost index (CPI) < 1, which means that the actual costs (ACWP) incurred were greater than the planned work costs (BCWP) so that the project experienced a cost deviation with a presentation of 0.92%. or 266,915,349.35 from the project budget, while for (SPI) the time performance index in the 18th week is <1, which means the project performance is slower than the planned schedule so that the project experiences a time deviation of 168 working days with an additional 42 working days from the scheduled implementation 126 working days so that the project was completed in the 24th week.